The game music toolbox : composition techniques and production tools from 20 iconic game soundtracks - Aristopoulos, Marios (New York : Focal Press, 2023)
The Game Music Toolbox provides readers with the tools, models, and techniques to create and expand a compositional toolbox, through a collection of 20 iconic case studies taken from different eras of game music. Discover many of the composition and production techniques behind popular music themes from games such as Cyberpunk 2077, Mario Kart 8, The Legend of Zelda, Street Fighter II, Diablo, Shadow of the Tomb Raider, The Last of Us, and many others. The Game Music Toolbox features: Exclusive interviews from industry experts Transcriptions and harmonic analyses 101 music theory introductions for beginners Career development ideas and strategies Copyright and business fundamentals An introduction to audio implementation for composers Practical takeaway tasks to equip readers with techniques for their own game music The Game Music Toolbox is crucial reading for game music composers and audio professionals of all backgrounds, as well as undergraduates looking to forge a career in the video game industry.
Keywords: Video game music -- Instruction and study; Video game music -- Analysis, appreciation; COMPUTERS / Computer Graphics / Game Programming & Design; GAMES / Video & Electronic